MUSCLE UNDER SIEGE: A CASE OF POST-BARIATRIC SURGERY RHABDOMYOLYSIS - Chun, Shi Hao; Nazlee, Asma’ Mohd; Chan, Pei Lin; Tan, Florence Hui Sieng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Rhabdomyolysis after bariatric surgery is rare and under-recognised. It can lead to acute kidney impairment with an associated 25% risk of mortality. We report a patient with rhabdomyolysis after sleeve gastrectomy. CASE A 48-year-old male patient who has class III obesity (body mass index of 70 kg/m²) was admitted for bariatric surgery. His medical history was significant for hypertension, gouty arthritis and moderate obstructive sleep apnea, with an American Society of Anesthesiologists (ASA) III physical status. He received 3 weeks of in-patient meal replacement therapy with a very low-calorie liquid diet and resistance exercise program before his operation. Intra-operatively, he was placed in a reverse Trendelenburg position. Initially, laparoscopic sleeve gastrectomy was planned, but a switch to open surgery was made due to technical difficulties. The total duration of surgery was 554 minutes. Post-operatively, the patient had a blister and grade II pressure injury at the left gluteus. He was oliguric (urine output less than 0.1 ml/kg/day) with elevated blood creatine kinase (>22,000 U/L at 36th-hour post-op) and stage 3 acute kidney injury (serum creatinine 360 umol/L). He was diagnosed with rhabdomyolysis and was co-managed with the nephrology team, whereby aggressive fluid replacement with diuresis was initiated. He did not require kidney replacement therapy throughout his course of recovery. On day 10 post-op, the laboratory findings normalised and the patient was discharged home fully recovered. CONCLUSION Postoperative rhabdomyolysis is a severe complication of bariatric surgery, which is potentially life-threatening. Creatine kinase testing should be performed in high-risk patients after bariatric surgery for timely diagnosis and interventions.